STUDY REGARDING THE PHYSICAL DEFICIENCY CORRECTING IN ANTERIOR-POSTERIOR PLAN BY EXERCISES, EXECUTED ON A MUSICAL BACKGROUND - Veronica Mindrescu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Along with music, exercise in general, were practiced in both prophylactic and curative purposes since ancient times until today. Through dance classes supported, I thought it can reach some of the most important objectives through means such as gymnastics, physical deficiencies preventing the onset of global and segmental training and maintaining proper body attitude. Between November 2014 and May 2015 have applied background music therapy movement, necessary correction of deficiencies related kyphosis anteroposterior closely monitoring the effectiveness of the therapy applied for six months. The research that we made included a group of 9 patients aged 8 to 14 years, 5 of which male patients and four female patients. The complex evaluation of patients held in kyphosis specific starting treatment and at the end of this treatment. For the assessment and diagnosis of kyphosis to be more precise we first conducted initial testing at baseline, then the final test at the end of treatment after a period of 6 months, after which we have seen a marked difference between the initial and final tests. Initial testing and final maximum distance between the cervical spine curvature and vertical plumb line between recovery averages is 9.88 mm. Dorsal and cervical dorsal curvature reached the dimensions considered normal in most patients initially diagnosed with kyphosis typical average kyphosis except 2 patients with atypical, where there was a slight improvement.